The Stereotypical Computer Scientist: Gendered Media Representations as a Barrier to Inclusion for Women. - Cheryan, Sapna; Plaut, Victoria; Handron, Caitlin; Hudson, Lauren (Sex Roles, 2013)
The present research examines undergraduates' stereotypes of the people in computer science, and whether changing these stereotypes using the media can influence women's interest in computer science. In Study 1, college students at two U.S. West Coast universities ( N = 293) provided descriptions of computer science majors. Coding these descriptions revealed that computer scientists were perceived as having traits that are incompatible with the female gender role, such as lacking interpersonal skills and being singularly focused on computers. In Study 2, college students at two U.S. West Coast universities ( N = 54) read fabricated newspaper articles about computer scientists that either described them as fitting the current stereotypes or no longer fitting these stereotypes. Women who read that computer scientists no longer fit the stereotypes expressed more interest in computer science than those who read that computer scientists fit the stereotypes. In contrast, men's interest in computer science did not differ across articles. Taken together, these studies suggest that stereotypes of academic fields influence who chooses to participate in these fields, and that recruiting efforts to draw more women into computer science would benefit from media efforts that alter how computer scientists are depicted.